THE MODEL OF MOTIVATING THE HIGHER EDUCATION FACULTIES OF UKRAINE BY EMPLOYING IT IN KNOWLEDGE SHARING TO IMPROVE ACADEMIC PUBLICATIONS - Burdiuh, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
Research and development are central to national and civilizational achievements. Research and development in any country is measured by the results of research, such as scientific publications. Scientific publications become the main criterion for evaluating teachers, as well as research and teaching staff of higher education institutions and research institutions. Knowledge is the most important resource in universities. Useful knowledge can improve the performance of employees in the organization. The exchange of knowledge or information exchange between employees is important for scientists and practitioners. Acquisition of knowledge, exchange of knowledge and use of knowledge are three types of knowledge management. Higher education in Ukraine seeks to strengthen research as a key component of the development of the nation and its universities. In recent years, higher education in Ukraine has initiated many projects to improve research on the productivity of research and teaching staff in Ukrainian universities. Ukrainian higher education seeks to automate all research activities to increase the effectiveness of research. This article discusses the impact of knowledge use. Joint use to improve the scientific publications of scientists and teachers of Ukrainian universities. In addition, this study identifies factors that lead to an increase in the level of knowledge exchange in Ukrainian universities. The author conducted an online interview with 350 representatives of the scientific and pedagogical staff of the Taras Shevchenko National University of Kyiv, studied scientific articles and websites of academic institutions to determine important indicators for measuring the productivity of scientific research. The results show that computermediated communication and the nature of knowledge are the main factors that positively affect the exchange of knowledge in Ukrainian universities. The author also concluded that scientific publications are a key indicator for measuring research performance. In addition, the exchange of academic knowledge and indirect communication significantly increases the productivity of research in Ukrainian universities.